Finding the beat entrainment, rhythmic play, and social meaning in rock music - Hesselink, Nathan (Bloomsbury Academic, 2022)
Introduces entrainment-the capacity to perceive a beat and synchronize to it-through the lens of contemporary rock music to explain why humans enjoy listening to music together and what is it about certain beats that captures our attention"--